Pemetaan Curah Hujan Dalam Upaya Mengurangi Resiko Bencana Hidrometeorologi Dengan Sistem Informasi Geografis (SIG) Untuk Wilayah Kalimantan Utara - Rachel Zandra Singal; Noptri Jumario (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2019)
North Kalimantan is one of the regions in Indonesia which is prone to hydrometeorological disasters. The purpose of this study was to determine the rainfall analysis of the North Kalimantan Region as a basis in finding rainfall levels in areas that do not have climatological stations, knowing the rainfall maps of the North Kalimantan Region and knowing the conditions of high rainfall causing flood prone in the North Kalimantan region. Rainfall data collection locations are climatology stations Tanjung Harapan, Juwata, Tuvai Semaring, Kalimarau and R.A. Bessing. Rainfall data is taken from OGIMET for 10 years. The result of rainfall analysis is the average monthly rainfall, which is from January to December. The method used to determine the monthly rainfall value in the North Kalimantan region is the Spatial Analyst Interpolation -Kriging method. The results are in the form of monthly rainfall maps, from January to December. Monthly rainfall map is a source of information on the value of rainfall in the region in North Kalimantan. Maximum rainfall is found in the areas of Tanjung Selor and Tarakan, namely January 313,368 mm, May 366,238 mm, July 358,868 mm and December 324,513 mm. Map of monthly rainfall in January, May, July and December is a parameter to see the condition of high rainfall causing hydrometeorological disasters. Through this research it is expected to anticipate the risk of disasters caused by the weather.